2012
DOI: 10.1016/j.jcrs.2012.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal astigmatism and axis location in cataract patients measured by total corneal power, automated keratometry, and simulated keratometry

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
0
28
2
Order By: Relevance
“…In peer-reviewed papers, the reported percentage of patients achieving an UDVA better than 20/40 after toric IOL implantation ranges from 70% to 100% (4,5,32,33) . Spectacle-independence for distance vision was reported by 60% to 85% of patients with unilateral toric IOL (3,6,31,34) and by 69% to 97% of patients with bilateral toric IOLs (7,8,35,36) . Reported percentages of patients with residual refractive astigmatism lower than 0.50 D range from 25% to 100% (9,10,37,38) .…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In peer-reviewed papers, the reported percentage of patients achieving an UDVA better than 20/40 after toric IOL implantation ranges from 70% to 100% (4,5,32,33) . Spectacle-independence for distance vision was reported by 60% to 85% of patients with unilateral toric IOL (3,6,31,34) and by 69% to 97% of patients with bilateral toric IOLs (7,8,35,36) . Reported percentages of patients with residual refractive astigmatism lower than 0.50 D range from 25% to 100% (9,10,37,38) .…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Previous studies have shown that manual keratometry, automated keratometry, simulated keratometry of Placido-based corneal topography, and simulated keratometry of Scheimpflug imaging provide similar values for anterior corneal curvature (28)(29)(30) , although significant disagreement in axis location has been reported (29) . Contrarily, anterior corneal astigmatism measurements differed significantly when comparing values derived from total corneal power and equivalent keratometry to that of automated, manual, and simulated keratometry (30,31) . These three later measurements are based only on the anterior corneal surface data, while the total corneal power and equivalent keratometry are based on the measurements of both the anterior and posterior corneal curvatures.…”
Section: Devicesmentioning
confidence: 99%
“…4,5 Contradicting results, however, have been reported. Srivannaboon et al, 6 for example, did not observe a compensatory effect of posterior corneal astigmatism but rather found that the total corneal astigmatism overestimated the keratometric astigmatism. Moreover, all previous studies included patients with minimal to low astigmatism (!1.00 D), whereas our attention should be focused on eyes with more than 1.00 D of corneal astigmatism; that is, the minimum amount of preoperative astigmatism that is usually corrected when a toric IOL is implanted.…”
mentioning
confidence: 96%
“…(20) Such vectorial astigmatism analysis is gaining popularity in literature in recent years, as an increasing number of articles employ it as analytical instrument. (1,4,7,8,21,22) Figure 4 compares mean magnitudes of pre and postoperative APV within each group and between groups. A statistically significant reduction in APV, considering preoperative and any postoperative APV, was found within each group (p value = 0.00).…”
Section: Discussionmentioning
confidence: 99%
“…(1) At least 15% to 20% of cataract patients have 1.50 diopters (D) or more of corneal astigmatism at preoperative evaluation.…”
mentioning
confidence: 99%